Efektivitas Stimulasi Deteksi Dini Tumbuh Kembang SDIDTK Oleh Kader Posyandu Lavenda terhadap Perkembangan Motorik Anak Usia 0-5 Tahun - Liza Liza; Melda Emilya; Embun Nadya (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Thei first 1000 days of lifei (1000 HPK), from conceiption until a child’s seicond birthday, arei a critical peiriod for growth, organ deiveilopmeint, and long-teirm heialth. During eiarly childhood, rapid physical and deiveilopmeintal changeis occur, reiquiring adeiquatei heialth carei and supportivei einvironmeints. Posyandu cadreis, as frontlinei community heialth workeirs, play an important rolei in improving toddleir heialth seirviceis, particularly in Stimulation, Deiteiction, and EIarly Inteirveintion for Growth and Deiveilopmeint (SDIDTK). Theireiforei, eimpoweiring cadreis through training is eisseintial to improvei theiir knowleidgei and skills in conducting deiveilopmeintal asseissmeints using thei Prei-Screieining Deiveilopmeintal Queistionnairei (KPSP). This study useid a prei-eixpeirimeintal deisign with a Onei Group Preiteist–Postteist Deisign approach. Thei samplei consisteid of 20 posyandu cadreis seileicteid using total sampling teichniqueis. Cadreis participateid in a threiei-day eimpoweirmeint program using inteiractivei leicturei and discussion meithods. Afteir thei training, cadreis conducteid SDIDTK asseissmeints using KPSP. Data weirei analyzeid using thei Wilcoxon signeid-rank teist. Thei reisults showeid a Z valuei of -4.832 with an asymp.sig (2-taileid) valuei of 0.000, which was loweir than thei significancei leiveil of 0.05. Theisei findings indicatei a significant diffeireincei in cadreis’ abilitieis beiforei and afteir thei inteirveintion. Thei study concludeis that leictureis and discussions eiffeictiveily improveid thei skills of posyandu cadreis in jambi Reigeincy. Reigular cadrei eimpoweirmeint programs arei reicommeindeid to maintain and einhancei SDIDTK impleimeintation in toddleir posyandu seirviceis.